Merancang Strategi Pembelajaran Agama Islam di SMP Negeri: Studi Kasus - Ihsan Zikri Ulfiandi; Nanang Qosim Al Masquri; Nur Khulailatul Hurriyah; Mulya Putra; Hasimi Jafar (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2023)
This study aimed to discover how Islamic Religious Education topic teachers construct learning strategies and identify difficulties in teachers who could be more capable of mastering learning strategies and approaches. A qualitative descriptive methodology is used in the investigation. Techniques for gathering data include interviews, observation, and documentation. In this research, data analysis takes the shape of words structured in a methodical, factual, and exact manner on the facts, nature, and relationships of the examined phenomena. The findings revealed that the teachers of the Islamic Religious Education subject at State Junior High School 7 Sungai Penuh considered choosing the right learning strategy, selecting media and learning tools, creating teaching evaluation tools, using methods and media, managing classes, approaching students, teaching facilities and supporting infrastructure, and a conducive learning environment when designing learning strategies. Even though some Islamic Religious Education professors are less capable of mastering various learning tactics and approaches, pupils need help to grasp the content offered. Before the learning process begins, Islamic religious education teachers have created learning plan designs.